HUBUNGAN DUKUNGAN KELUARGA DENGAN MOTIVASI IBU DALAM MENDAPATKAN IMUNISASI DASAR LENGKAP PADA BAYI USIA 0-12 BULAN DI DESA NYABAKAN BARAT - Rifmi Utami; Zakiyah Yasin; Ika Sulistiorini (Fakultas Ilmu Kesehatan, 2015)
The immunization program was one of the primary prevention to avoided infectiondisease. The problems of in this study was lack coverage complete basic immunization in thevillage of West Nyabakan 2014. The purpose of this study to analyzed the family support withmother motivation to got complete basic immunization in infants aged 0-12 months.This kind of research was a Cross Sectional Study of Analytical correlations. The acountpopulation was whole of mother as many as sixty one people and the acount of samples wassome mothers as many as fivety thre epeople with used by probability sampling techniquetype of simple random sampling. The dependent variable was family support and theindependent variable was mother motivation. Collect of data used by approvals sheets andquestionnaires. Data processing used by the editing, coding, scoring, data entry, tabulationof data and used by spearman correlation test.The results showed that almost half of the group of mothers got a good family support(44%) and almost half have a strong motivation (42%). Statistical test results obtained Pvalue <α (0.000 <0.05), and the 95% confidence level. The strength of the correlation was rof 0.892 which means that the strength of the relationship between variables was verystrong.It could be concluded that there wasa significant relationship between family supportwith mother motivation. It was better family support so the stronger mother motivation got acomplete basic immunization. So it was very recommended to health care workers to payattention family support because the family support was very associated with motivation.Keywords : Support Family, Mother Motivation, Complete Basics Immunization